PERSENTASE KEPATUHAN DOKTER DALAM PENULISAN RESEP SESUAI FORMULARIUM OBAT OBAT TERTENTU DI RSU AL-ISLAM H.M MAWARDI PERIODE OKTOBER-DESEMBER 2018 - Rizky Arif; Nina Budianti (AFAMEDIS, 2021)
Abstract Hospital Formulary is prepared referring to the National Formulary. Hospital Formulary is a list of medicines agreed by medical staff, compiled by the Committee / Team of Pharmacy and Therapy established by the Hospital Management. Certain medicines that are often misused, hereinafter referred to as Certain Medicines, are medicinesthat work in the central nervous system other than Narcotics and Psychotropic, which in use above the therapeutic doses can cause dependence and specific changes in mental and behavioral activities. The objective of this study is to determine the percentage of doctor’s compliance in prescribing according to the formulary of certain drugs in the Al-Islam General Hospital H.M Mawardi from October to December 2018. This study uses a simple random sampling technique by counting the number of samples using the Slovin formula. Random sampling is taken every month as many as 100 prescriptions that are intended to determine the percentage of doctor's compliance in writing prescription of certain drugs according to the hospital formulary. Based on the research conducted at RSU Al-Islam H.M Mawardi, it can be concluded that in writing prescription of certain medicines, of 287 prescriptions (95.7%) were in accordance with the hospital formulary. And 13 prescriptions (4.3%) were not in accordance with the hospital formulary.